484 Exploratory observational quantification of liver abscess incidence, specific to region and cattle type, and their associations to viscera value and bacterial flora. (7th December 2018) - Herrick, R; Rogers, C; McEvers, T; Amachawadi, R; Nagaraja, T; Maxwell, C; Lawrence, T
Abstract: Liver abscesses in finished cattle have been a topic of interest since the 1940's. Our objective was to quantify incidence and economic impact of liver abscesses and identify predominant bacterial species specific to: severity of abscesses, sampling location, and cattle type. Observational liver audits occurred at 7 fed beef (n = 130, 845 livers) and 4 cull cow (n = 30, 646 livers) processing facilities. At each facility, 30 (10 A-, 10 A, 10 A+) intact liver abscess samples were collected and cultured for Fusobacterium necrophorum, Trueperella pyogenes, and Salmonella enterica . Outcome frequency and economic data were analyzed using the GENMOD procedure of SAS v9.4 (SAS Inst. Inc., Cary, NC), with fixed effects of region, cattle type or liver score. Average liver abscess incidence was 20.3% and 17.6% for cattle harvested at fed beef processing facilities, for cull beef processing facilities, respectively. Fed Holsteins had greater ( P < 0.01) abscess incidence rates (25.0%) than fed beef steers (18.2%) or heifers (19.1%). Cull dairy cows, cull bulls, and cull range cows had total abscess incidence rates (19. 8%, 19.3%, and 16.7%, respectively) similar to fed steers and fed heifers. Fusobacterium necrophorum subsp. necrophorum was present in 79.9% of samples collected from fed beef processors and 76.9% of samples from cull beef processors whereas Trueperella pyogenes was present in 14.8% of samples from fed beef processors and 8.8% of samples from cull beef processors. Salmonella enterica was present in 27.5% of abscess samples collected from fed beef processors and 16.5% of samples from cull cow processors. Total visceral losses ($/animal) did not differ by region ( P = 0.48) or cattle type ( P = 0.86), yet conservative estimates indicate that liver abscesses and other liver abnormalities cost the beef industry approximately $60 million annually in viscera losses.